Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan Pada Elzatta Probolinggo - Yayuk Indah Wahyuning Tyas (Ecobuss, 2020)
Abstract: This study discusses Liquidity Ratio Analysis, Solvency, Activity and Profitability. To assess Elzatta's Financial Performance, the purpose of this study is to determine the condition and performance based on financial ratios. The data used are primary data and secondary data. This type of research is a type of quantitative descriptive research that aims to find factual information. The object used in this study is the financial statements in the form of Balance Sheet and Loss Reports for the 2018 and 2019 periods. The data analysis method used is the quantitative data analysis method. The results of the study are seen from the liquidity ratio and the solvency ratio of the Debt to Asset Ratio in 2018 to 2019 which is very good. If seen from the Elzatta effectiveness level ratio based on inventory turnover in 2018 until 2019 in carrying out its operations it can be said to be effective. Profitability ratios can be seen from the Return on Investment and Return on Equity and the analysis of profitability ratios that have been carried out in 2018 until 2019 has increased. Keywords: Financial performance and financial statements